On the Methodology of Modern Russian Law - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2023)
An analysis of modern Russian literature made it possible to identify two equally negative tendencies in the methodology of jurisprudence. The first is that legal scholars pay little attention to methodology; the second is in attempts to introduce new methods into the methodology that are not used in practice.